Genetic and environmental influences on the developmental trajectory of callous‐unemotional traits from childhood to adolescence. (17th May 2020) - Takahashi, Yusuke; Pease, Christopher R.; Pingault, Jean‐Baptiste; Viding, Essi
Abstract : Background: This study examined the genetic and environmental influences underlying baseline level and developmental course of callous–unemotional (CU) traits across childhood and adolescence. Methods: The data on 8, 958 twin pairs (3, 108 MZ twin pairs and 5, 850 DZ twin pairs) from the Twins Early Development Study were analysed. CU traits were assessed at ages 7, 9, 12 and 16 by mothers and analysed using a biometric latent growth model. Results: Individual differences in the baseline level of CU traits were highly heritable (76.5%), while the heritability of the developmental course of CU traits was moderate (43.6%). The genetic influences on baseline level and developmental course of CU traits were mostly nonoverlapping. Nonshared environment made a modest contribution to the baseline level of CU traits (21.7%). Nonshared environmental influences on the developmental course of CU traits were moderate (43.2%), with nearly half of them being the same as those influencing the baseline level and just over half being specific. Shared environmental effects did not contribute to systematic change across childhood and adolescence but were rather age‐specific. Conclusions: Our findings demonstrate that rather than only being conceptualized as factors of stability, genes also play a dynamic role in explaining systematic change in CU traits. Genetic effects for the initial risk and subsequent development of CU traits are not the same. In addition to genetic factors, nonshared environmental influences play an important role in explaining why some children will increase or maintain their CU traits over time, whereas other will desist. New genetic and environmental influences with age suggest that repeated, age‐tailored interventions may be required throughout development to make a lasting difference in the presentation of CU traits and associated outcomes.